Nurse competencies in caring for the Covid-19 patient on invasive mechanical ventilation in hospital care: scoping review (Research, Society and Development, 2022)
Objective: systematically map the skills necessary for nurses to work in the care of patients with Covid-19 in invasive ventilatory support. Methodology: Scoping Review study based on a set of techniques to systematically map knowledge production according to reviewer's manual for scoping reviews developed by the Joanna Briggs Institute. Results: for the selection of studies we follow according to the protocol created and attached on the OSF platform according to jbi guidelines and criteria; were identified by searching the databases, a result of 2,104 studies, these were sent to the endnote® bibliography management software, to organize references and remove duplicate references, identifying one (N) of 28 duplicate studies and rayyan one (N) of 32 duplicate studies, totaling 60 studies. Next, the process of reading title and abstract was started with a result of (N) of 2,044 studies, one (N) from 1977 was excluded, quantifying one (N) of 67 studies for reading and analysis in full, after excluding one (N) of 52 studies, obtaining a final result of (N) from 7 selected studies. Conclusion: Because it is a Scoping Review, this method meets the demands of synthesizing evidence of broad research issues and the reliability of your data. Although this methodology does not evaluate the quality of evidence and thus is limited to providing a descriptive narrative or report, it is believed that it can contribute to clinical decision-making and care improvement in the face of the Covid-19 pandemic.